Pattern Recognition Method to Predict Recycling Strategy for Electronic Equipments - M. M., Noor; M. M., Rahman; K., Kadirgama; M. A., Maleque (2011)

(untitled)
The environmental problem is an extensive, complex problem, and some example areas of study are energy consumption, material/resources use, recycling, and environmentally relevant substance control. Life cycle engineering is the engineering and design of products and processes to minimize the cost and environmental impact for the life cycle phases of a product. Functional Radial Basis Function Networks (FRBFN) is used to determine recycling strategy (reuse, service, remanufacture, recycle with disassembly, recycle without disassembly and disposal). Seven parameters (wear - out life, technology cycle, level of integration, number of parts, reason for redesign and design cycle) were considered as the input for the FRBFN model. Eight equipments were selected to be examined such as vacuum cleaner, washing machine and television. All the results verify previous literature study. The prediction model predicts the end life strategies quite closely with best industry practices but only 25 % match average industry practices.